Visual-graphic spiral pattern can reduce medical-associated stress during the geomagnetic storm - Katamanova, Djemilya; Sataieva, Tatiana; Rybalko, Sergei; Rebik, Anastasia; Tsapik, Dmitriy; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Introduction. About 18% of all health problems in the working population are related to stress, depression and anxiety. The consequences of industrial stress exacerbated by unfavorable geomagnetic activity, can manifest itself in an increase in the psychophysiological “price” of activity, overstrain and depletion of the regulatory mechanisms of functional systems that ensure the adaptation of the body to vital factors and, ultimately, in a significant deterioration in the health of workers. Medical workers occupy a special place in the structure of professional groups of the working population, since they are at increased risk of neuro-emotional overstrain up to the development of professional burnout syndrome. The aim of the study is to develop and test a technique that helps to reduce the level of stress and emotional load affecting the psychophysiological state of a person. Materials and methods. The study involved 15 relatively healthy medical students aged 19 to 25 years. The algorithm of the study was as follows: the forecast of geomagnetic storms (G3-5) was tracked on the website of the Laboratory of X-ray Astronomy of the Sun (https://tesis.lebedev.ru /). During the storm a student was given the graphic task, in the form of synchronous outlines of stencils with two hands, before and after completing the experimental task the subject was asked to pass psychological tests: a visual-analog scale of situational emotional state according to the Dembo-Rubinstein method and the Spielberger-Khanin scale of personal and situational anxiety (STAI). The electroencephalogram was recorded using an electroencephalograph recorder "Encephalan-EEGR-19/26". Results. The Dembo-Rubinstein technique showed that after passing the experimental task 21% of the subjects significantly improved their emotional state according to a quantitative assessment of the visual-analog scale of situational emotional state. The level of personal anxiety also significantly decreased by 5% and the level of situational anxiety did not change, the assessment was carried out using the Spielberger-Khanin scale of personal and situational anxiety (STAI). Limitations. The obtained results require further verification on the larger experimental groups with the involvement of medical workers of different age and specialties; lengthening the period of observation of the recorded indicators after completing of the tactile-graphical task to clarify the timing of changes in indicators of situational emotional state and personal anxiety. Conclusions. A simple technique for reducing stress levels in medical students has proved its effectivity in changing the psychophysiological manifestation of stress, since the level of stress activity is directly related to the degree of personal anxiety. This technique can be recommended to medical workers and students as an exercise to improve cognitive activity by reducing stress and anxiety associated with the influence of geomagnetic storms, which increase sensitivity to external stress factors, on the psychophysiological state of a person.